Rainy cycles in South America as a driver for the breeding of the Black Skimmer (Rynchops niger) and the Large-billed Tern (Phaetusa simplex) (Aves, Charadriiformes) - Ariane Campos Gouvêa; Gustavo A. Bravo; Paulo de Tarso Zuquim Antas; Karl-L. Schuchmann; Luís Fábio Silveira (Papéis Avulsos de Zoologia, 2023)
Abstract The Black Skimmer (Rynchops niger) and the Large-billed Tern (Phaetusa simplex) are two migratory waterbirds that breed simultaneously on many river beaches in South America. Both are polytypic taxa with little information about the distribution and nonbreeding (“wintering”) areas. Based on data from the literature, citizen science websites, fieldwork, and specimens housed in natural history museums, we revised the distribution of some of the main breeding colonies in South America, comparing it with continental rainy cycles to identify generalities about the role of precipitation seasonality on the defining intratropical migration routes of these species. Our data suggest that the seasonal precipitation cycle of South America directly influences the reproductive timing and distribution of both species, which is largely circumscribed by South America’s rivers. After breeding on sandy beaches during the dry season, both species disperse in small groups or even individually - not in large flocks as seen in breeding areas - making it difficult to find general migration patterns during the rainy season. Nonetheless, individuals of both species tend to follow the course of the largest rivers of the continent and even alternative routes to disperse into several areas throughout South America during the nonbreeding season.